Automated incident detection in surveillance systems - Motiwala, Murtaza; Ahmed, Shupriyo Shafkat; Ahmed, Sabrina (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.